Corbella, Dolores; Fajardo, Alejandro y Langenbacher-Liebgott, Jutta (eds.), Historia del léxico español y Humanidades digitales, Berlín, Peter Lang, 2018, 498 pp. - Junquera Martínez, Alejandro (Estudios Humanísticos. Filología, 2020)
Resumen/abstract